PEMBELAJARAN BAHASA INGGRIS YANG MENYENANGKAN MELALUI PEMAHAMAN GAYA BELAJAR SISWA - Anita Tri Rahayu; Imam Sibawaih (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2017)
Abstract: his article explain the learning style of the students, and their preference related to their learning style in Joyfull English Learning. Most of the students are difficult in learning cause they do not know their learning style. Furthermore, it is found that most of the students like the teachers less comprehend the students’ learning style in learning so that students are difficult in learning. Then, they like teachers give correction and be angry if the students could not answer the teacher’s ask. This article will discuss how the students learn based on their learning style.